Frequency and prognostic impact of antibodies to aquaporin-4 in patients with optic neuritis - Jarius, Sven; Frederikson, Jette; Waters, Patrick; Paul, Friedemann; Akman-Demir, Gulsen; Marignier, Romain; Franciotta, Diego; Ruprecht, Klemens; Kuenz, Bettina; Rommer, Paulus; Kristoferitsch, Wolfgang; Wildemann, Brigitte; et al. (Journal of the neurological sciences, 2010)
Background - Antibodies to aquaporin-4 (AQP4-Ab) are found in 60-80% of patients with neuromyelitis optica (NMO), a severely disabling inflammatory CNS disorder of putative autoimmune aetiology, which predominantly affects the optic nerves and spinal cord. - Objective - To assess the frequency of AQP4-Ab in patients with optic neuritis (ON), and to investigate the prognostic implications of AQP4-Ab seropositivity in such patients. - Patients and methods - AQP4-Ab serum levels were determined in 224 individuals from Austria, Denmark, France, Germany, Italy, and Turkey using a newly developed fluorescence immunoprecipitation assay employing recombinant human AQP4. - Results - AQP4-Ab were detectable in 8/139 (5.8%) patients with acute monosymptomatic optic neuritis (AMON) and in 10/17 (58.8%) patients with established NMO and a last relapse of acute ON (NMO/ON), but not in 32 patients with multiple sclerosis or in 36 healthy controls. At last examination, 4/8 (50%) seropositive AMON patients had met the criteria for NMO but 0/128 seronegative AMON patients. Disease severity differed significantly between seropositive and seronegative AMON. Complete bilateral or unilateral blindness occurred in six AQP4-Ab positive patients, but only in one AQP4-Ab negative patient. AQP4-Ab levels did not vary between seropositive AMON and NMO/ON and did not correlate with disease severity. Female gender, a relapsing course, and concomitant autoimmunity were associated with AQP4-Ab seropositive status and risk of developing NMO. - Conclusion - AQP4-Ab is relatively rare among patients with AMON, but if present it predicts a high rate of conversion to NMO within one year.